The transfer of Cadmium from rock to soil and the associated vegetation cover under natural conditions at the Swiss Jura Moutains - Quezada Hinojosa, Raul Percy (My University, 2010)
As a result of soil-surveying studies conducted in the Swiss and French Jura Mountains during the early 1990's, anomalous cadmium (Cd) concentrations were identified in soils developed mostly on Bajocian and Oxfordian limestone. Measured Cd concentrations exceed in most of the cases the Swiss official tolerance guideline concentration for non-polluted soils established at 0.8 mg⋅kg-1. Several research works have confirmed the geogenic origin of Cd in soils derived mainly from the weathering of a Cd-rich carbonate substrata. Cd is a highly toxic trace element and the pedogenic / physicochemical conditions leading to its transfer from rocks to soils and its potential bioavailability to plants are in need of a detailed geochemical assessment. The aim of the present work is to complete the geochemical database by studying rock-soil-plant interactions with regard to this element under natural conditions in two specific sites. A first study of rock-soil interaction was carried out determining Cd-bearing phases in a soil developed on top of a road-cut section outcropping at the SW-facing slope of the Schleifenberg hill (canton Basel-Land, Switzerland). This section consisting of an oblique succession of Bajocian oolitic carbonate includes several horizons which are anomalously enriched in Cd (0.03–4.90 mg⋅kg-1). Cd contents in this soil are in the 0.3–2.0 mg⋅kg-1 range. Vertical pedogenetic processes (weathering of underlying bedrock) as well as lateral colluvial limestone (weathering of uphill carbonates) are responsible for the origin of Cd in the soil. Half of the Cd still resides in the carbonate fraction, while the Cd released from the weathered carbonates is associated either with organic matter (over 10%) or with Fe and Mn-oxyhydroxides (approximately 30%). Adsorption of a low percentage of Cd on clays is of less importance since Pb, Zn, Cu and Cr ions will compete with Cd to gain adsorbed sites on clays. No exchangeable Cd phase was found and this, together with the buffer capacity of this calcareous soil, suggests that the amount of mobile Cd is quite negligible, which also greatly reduce the amount of bioavailable Cd. Where developed on steep slopes, the soil will hardly accumulate and colluviums will constantly renew it. A second study regarding the transfer and distribution of geogenic Cd in the soil was conducted on six closely spaced soil profiles at the site called Le Gurnigel (canton Neuchâtel, Switzerland). The soils consist mainly of cambisols and cambic-neoluvisols showing an important allochthonous, aeolian fraction. Cd concentrations generally increase down the soil profiles, showing maxima (up to 16.3 mg⋅kg-1) near the soil-bedrock interface. Most Cd resides in the carbonate and organic fractions in topsoils, whereas the amorphous oxyhydroxides fraction becomes the most important Cd-bearing phase in the middle and in subsoils. Cd, Zn and Cr are positively correlated with comparable distributions in the soil profiles suggesting a common bearing phase such as Fe oxyhydroxides for these three elements. A complex transfer pattern of Cd starts with the release of Cd from the underlying bedrock, and then transferred into oxide, hydroxide, carbonate and organic phases. Additionally, the lateral advection of Cd-rich soils formed on steep slopes acts as a local allochthonous input of Cd to these soils, which in turn is transferred from the topsoil towards the deeper horizons by biological and pedogenic processes. The amount of readily exchangeable and therefore potentially bioavailable Cd is low in these soils (on average 0.2 mg⋅kg-1) provided that the pH remains above 5. Under stronger acidic and oxidizing conditions, Cd bound to organic matter may be mobilised and the bioavailability of Cd would range between 3.3–5.4 mg⋅kg-1 in cambisols and reach up to 1.7 mg⋅kg-1 in deeper cambic-neoluvisols. Soil-plant interactions were studied at the Le Gurnigel analyzing six local plants chosen for their ubiquity in the studied soil profiles. Cadmium accumulation was separately determined in roots and shoots. Three herbs, two graminoids and a tree were used for this purpose. They showed that the accumulation of Cd varies from one species to another and even between plants from the same family. Global levels of Cd in the selected vegetation are in the 2–6 mg·kg-1 range, thus exceeding the official limit value of Cd concentration tolerated in vegetal food for animals established at 1 mg·kg-1. The different behaviours were compared as a function of the variability of Cd in soils. A rise in the concentration of Cd in the soil progressively reduces the transport of Cd toward the shoots reducing also the yield production and increasing the accumulation of Cd in roots. Transfer coefficients from soil / rhizosphere to plant are inversely proportional to the total Cd concentration in soils and do not depend on species identity but instead on soil type. Sequential chemical extractions revealed that variations of Cd distribution between distant soil and rhzosperic soil occur mainly in the first three Cdbearing phases due principally to the incorporation of roots exudates that modify pH and redox conditions of the rizhosphere. High levels of Cd (up to 9 mg·kg-1) were found in shoots of three of the studied plants and may represent a mid-term hazard for animals and human health since these plants are used either for grazing of cattle or for medical purposes. The phenomenon of natural enrichment of soils with geogenic Cd and its progressive accumulation in vegetation covers is suspected to have a widespread occurrence elsewhere, as a function of frequent outcrops of Cd-enriched carbonates of Bajocian and Oxfordian age in western and southern Europe principally in France, Spain and Italy.
Thèse de doctorat : Université de Neuchâtel, 2010
Keywords: Cadmium; Bioavailability; Geogenic; Natural pollution; Late-Bajocian carbonates; Plant; Rhizosphere; Soil; Sequential Extraction